The relationship between consciousness and the ascending reticular activating system in patients with traumatic brain injury - Jang, Sung Ho (BMC Neurol, 2020)
BACKGROUND: We investigated the relationship between consciousness and the ascending reticular activating system (ARAS) by using diffusion tensor tractography (DTT) in patients with traumatic brain injury (TBI). METHODS: Twenty-six patients with TBI and 13 healthy control subjects were recruited for this study. Glasgow Coma Scale (GCS) scores were used for evaluation of subject consciousness state at the chronic stage of TBI (at DTT scanning), According to the GCS score, the patient group was divided into two subgroups: A (14 patients;impaired consciousness: GCS score < 15, and B (12 patients;intact consciousness;GCS score = 15). Fractional anisotropy (FA) and tract volume (TV) values were assessed in the lower dorsal and upper ARAS. RESULTS: The FA values of the lower dorsal ARAS and the upper ARAS in patient subgroup A were significantly lower than those in patient subgroup B and the control group(p <  0.05). However, the FA and TV values for the lower dorsal ARAS and the upper ARAS were not significantly different between patient subgroup B and the control group(p > 0.05). The FA value of the lower dorsal ARAS(r = 0.473,p <  0.05) and the TV of upper ARAS(r = 0.484,p <  0.05) had moderate positive correlations with the GCS score. The FA value of the upper ARAS had a strong positive correlation with the GCS score of the patient group(r = 0.780,p <  0.05). CONCLUSIONS: We detected a close relationship between consciousness at the chronic stage of TBI and injuries of the lower dorsal and upper ARAS (especially, the upper ARAS) in patients who showed impaired consciousness at the onset of TBI. We believe that our results can be useful during the development of therapeutic strategies for patients with impaired consciousness following TBI. TRIAL REGISTRATION: YUMC 2019–06–032-003. Retrospectively registered 06 Jun 2020.